Recent Publications (Quarterly Journal of Economics, 1944)
Recent Publications Get access The Quarterly Journal of Economics, Volume 58, Issue 4, August 1944, Pages 651–653, https://doi.org/10.1093/qje/58.4.651 Published: 01 August 1944